The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1021/acsomega.1c01538
|View full text |Cite
|
Sign up to set email alerts
|

Thermoelectric Properties of Pristine Graphyne and the BN-Doped Graphyne Family

Abstract: In this paper, we have investigated the thermoelectric properties of BN-doped graphynes and compared them with respect to their pristine counterpart using first-principles calculations. The effect of temperature on the thermoelectric properties has also been explored. Pristine γ-graphyne is an intrinsic band gap semiconductor and the band gap significantly increases due to the incorporation of boron and nitrogen atoms into the system, which simultaneously results in high electrical conductivity, a large Seebec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…g) Seebeck coefficient comparison of GBNS and GBNM with various samples 1‐pristine ϒ‐graphyne, 2‐ϒ graphyne with BN at the chain, 3‐ϒ graphyne with BN at the ring, and 4‐ϒ graphyne like BN sheets. [ 59 ] h) Simulation result of thermoelectric output power density with the variation of thickness of coating materials for GBNS and GBNM hybrid materials. i) Schematic diagram of Au/Gr/BN/Gr/Au device structure for tunneling current measurement, where Gr layer varies from 1 to 10 layer.…”
Section: Resultsmentioning
confidence: 99%
“…g) Seebeck coefficient comparison of GBNS and GBNM with various samples 1‐pristine ϒ‐graphyne, 2‐ϒ graphyne with BN at the chain, 3‐ϒ graphyne with BN at the ring, and 4‐ϒ graphyne like BN sheets. [ 59 ] h) Simulation result of thermoelectric output power density with the variation of thickness of coating materials for GBNS and GBNM hybrid materials. i) Schematic diagram of Au/Gr/BN/Gr/Au device structure for tunneling current measurement, where Gr layer varies from 1 to 10 layer.…”
Section: Resultsmentioning
confidence: 99%
“…2D-materials have gained significant attention during the present decade because of their novel electronic, optical, and mechanical properties compared to those of their corresponding bulk counterparts. These 2D materials are widely used in several technological applications including nanoelectronics, ,,, optoelectronics, , spintronics, , thermoelectric devices, energy storage, , hydrogen storage devices, electrodes in batteries, gas sensing, solar cells, catalysts, etc. because of their large surface area, high mechanical and chemical stability, and enriched electrical conductivity .…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have explored the structural and optoelectronic properties of BN-doped graphynes with different configurations. 31,32,43,44 Inspired by the above studies, we selected graphyne as the parent for BN substitution and constructed five BN pair-substituted graphyne systems. We then explored the effect of alkali metal (Li, Na, and K) doping on the electronic and NLO responses of hybrid systems.…”
Section: Introductionmentioning
confidence: 99%
“…Over the years, many potential applications of BN pair-doped graphyne derivatives have been systematically studied. For instance, BN-codoped GDYs can be used as promising electrocatalysts , and chemical nanosensors, and BN-doped graphynes are excellent candidates for UV light protection and thermoelectric applications . Besides, BN pair doping proved to be an efficient strategy to enhance the NLO responses of compounds (such as graphene, biphenylene, heterofullerene, and carbon nanotube). It is also found that the type and size of the BN domain have a significant effect on the β 0 value of the hybrid CNT system .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation